2009
DOI: 10.1097/lgt.0b013e31817ff92a
|View full text |Cite
|
Sign up to set email alerts
|

Inner Border-A Specific and Significant Colposcopic Sign for Moderate or Severe Dysplasia (Cervical Intraepithelial Neoplasia 2 or 3)

Abstract: Inner border is a rare colposcopic phenomenon but highly specific for CIN 2 or 3 in young women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 7 publications
1
8
0
Order By: Relevance
“…We analyzed these specific signs in detail, and the specificity and PPV of both signs were high. Other studies have confirmed the clinical utility of these criteria and their strong association with HSIL [ 22 25 ]. With regard to other minor changes and major changes , the incidence of a thin acetowhite epithelium was the highest (65.4%).…”
Section: Discussionmentioning
confidence: 75%
“…We analyzed these specific signs in detail, and the specificity and PPV of both signs were high. Other studies have confirmed the clinical utility of these criteria and their strong association with HSIL [ 22 25 ]. With regard to other minor changes and major changes , the incidence of a thin acetowhite epithelium was the highest (65.4%).…”
Section: Discussionmentioning
confidence: 75%
“…Introduction of the two new signs, "inner border sign" and "ridge sign" to the grade 2 (major lesions) section, was the result of their significant validity as markers of high-grade cervical intraepithelial neoplasia. 22,23 Sharp border has also been associated with a more severe lesion. The term leukoplakia or keratosis was considered a major lesion in the first and second International Federation of Cervical Pathology and Colposcopy terminologies 2,3 but was reclassified in 2002 in the third International Federation of Cervical Pathology and Colposcopy terminology, 4 under "miscellaneous findings," to diminish its significance.…”
Section: Discussionmentioning
confidence: 95%
“…Overall, the new colposcopic nomenclature more clearly emphasises the significance of colposcopic examinations than did the preceding version. Especially gratifying is the fact that two current publications from Germany-speaking countries (Scheungraber et al [3,4]) have been duly incorporated in the revision of the nomenclature. It should also be mentioned that the practically important differentiation between the localisation of lesions inside and outside of the transformation zones has been explicitly described in the nomenclature and also that the significance of the surface expansion of dysplasia in cervix uteri has been scientifically confirmed by publications from German-speaking countries [10,11].…”
Section: Zusammenfassungmentioning
confidence: 99%
“…It should be noted critically that making the diagnosis of metaplasia actually necessitates a prior histological clarification in order to prove the existence of the metaplasia and exclude other functional findings, e.g., hyperplastic or polypous ectopy. In abnormal colposcopic findings, the localisation of the lesioninside or outside the transformation zonehas been re-included in the nomenclature and supplemented with the terms "inner border" (border within the acetic-white epithelium) and "ridge sign" [3,4]. The size of the lesion has been incorporated in the nomenclature whereby the dimensions of the lesion are to be given as number of afflicted quadrants or, respectively, as percentage of the cervix.…”
Section: Zusammenfassungmentioning
confidence: 99%